A Comparative Analysis Based on Economic Factors of Students Emigration from South Asia - Khan, Yasir; Hassan, Taimoor; Yi, Wang Ming; Gulzar, Rahimullah (Asian Journal of Economics and Empirical Research, 2018)
Economic instability and higher unemployment significantly increased the number of students migration from all over the world, particularly South Asian countries in the last decade. Growing number of international student migration to abroad for higher education and search for better economic opportunity. This study will determine the economic impact of students’ emigration from South Asian countries particularly Pakistan, India, and Bangladesh. A comparative analysis of the three border sharing countries have shown the long-term economic and political instability and a result of an economic and financial collapse in 2008, and also discuss how such an environment has affected student emigration from South Asia. This study is quantitative research using questioners as a tool to collect primary data, from the large sample size of 300 South Asian students studying in Chinses universities in China. This research work is based on two factors, 1) the deterioration of economic factors in Pakistan, India, and Bangladesh have changed the students’ perception to migrate abroad; 2) the study also reflected that majority of Pakistani, Indian and Bangladeshi students want to stay in the host country. The findings indicated that all the related variables have significantly positive, economic instability, higher unemployment, lower salary, political instability, and lower quality education system. The logit-probit regression models with these variables could predict the higher value of the variance in the overall student migration to abroad. Findings are relevant for academic institutions and government agencies interested in international education, student migration behavior, comparative data as well as strategic policies.